Antibacterial activity and compound identification of Eurya acuminata leaf fractions against bacteria-causing skin infections - FESKAHARNY ALAMSJAH; ANTHONI AGUSTIEN; ARTHAULY YOPITA SINURAT; MUFIDHATUL MUQARRAMAH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Alamsjah F, Agustien A, Sinurat AY, Muqarramah M. 2024. Antibacterial activity and compound identification of Eurya acuminata leaf fractions against bacteria-causing skin infections. Biodiversitas 25: 3441-3448. Antibiotics previously used to treat skin infections have recently been ineffective due to pathogenic bacteria resistance, and the discovery of antibacterial agents derived from medicinal plants is a breakthrough. Eurya acuminata DC. is a member of the Pentaphylacaceae family and has efficacy values as a medicinal plant used in traditional medicines. This study aims to analyze the antibacterial activity of fractions (hexane, ethyl acetate, and water) of E. acuminata against bacteria causing skin infections and identify the chemical components of active fractions. A diffusion test was conducted for the antibacterial test. TLC (Thin Layer Chromatography) was used to determine the chemical components of the fractions. The fraction with the highest level of antibacterial activity was subjected to additional analysis using diffusion and LC-MS/MS (Liquid Chromatography-Mass Spectrometry/Mass Spectrometry). The antibacterial test showed that hexane, ethyl acetate, and water fractions were active against bacteria, with the ethyl acetate fraction having the highest activity. The TLC profile and the diffusion assay of the ethyl acetate fraction showed that spot number 4 with an Rf 1,00 had antibacterial activity. Identification of the compounds of the ethyl acetate fraction by LC-MS/MS resulted in identified compounds such as acacetin, kaempferol, peonidin, chrysoeriol, nobiletin, luteolin, and antroquinonol. This study demonstrates a new hope for further research into natural antibacterial agents, and it is a breakthrough with these phytochemicals.